The impact of genre-based instruction on Saudi university students’ English writing performance and motivation: a mixed-method study - Abdel Latif, Muhammad M. M.; Alghizzi, Talal Musaed; Alshahrani, Tahani Munahi (Frontiers in Psychology, 2024)
Despite the important role motivation plays in students' writing learning and development, not much attention has been given to experimenting particular instructional techniques for developing students' writing motivation. One of the least researched teaching techniques in writing motivation studies is genre-based instruction. In this study, we examined the impact of genre-based instruction on 21 Saudi university students' English argumentative and classification essay writing performance and their writing motivation dimensions (writing apprehension, anxiety, self-efficacy and self-concept). Drawing upon the quasi-experimental research design and non-random sampling technique, we used genre-based instruction with a representative intact class of English-as-a-foreign-language (EFL) writing students at a Saudi university. To examine the potential impact of the treatment, we collected pre-and postinstruction data, along with a post-course open-ended questionnaire. The results showed that genre-based instruction has contributed significantly to improving the students' writing performance and also their writing motivation dimensions. These positive gains varied from one writing quality aspect and motivational variable to another. The students' answers to the open-ended questionnaire also showed the positive writing learning and motivation improvements they experienced. It is generally concluded that developing students' language and rhetorical awareness and text composition performance seems to be a prerequisite for improving their writing motivation levels. The paper ends with discussing the implications of the results.